The level of cyberbullying and its impact on the academic achievement of male and female secondary school students in Riyadh from their point of view - Aljasser, Arwa Abdullah (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to identify the impact of cyberbullying on the academic achievement of male and female secondary school students. And discovering the differences between males and females in the influence of the degree of electronic bullying on the academic achievement of male and female secondary school students. And to identify the differences between secondary school grades in the influence of the degree of cyberbullying on the academic achievement of male and female students, and to discover the effect of the quality of the educational environment on the degree of cyberbullying on the academic achievement of male and female secondary school students. The researcher utilized the social survey method to collect the required data through a questionnaire. The sample of the study was a simple random sample consisting of (100) students.) a male and female secondary school student and reached the results: 1- The level of cyberbullying among secondary school students was very high, as the general average was equal to (4.25) and the degree of agreement was (strongly agree), with a standard deviation of (0.82). 2- Level The decline in academic achievement among secondary school students was very high, as the general average was equal to (4.27) and the degree of agreement was (strongly agree), with a standard deviation of (0.91). 3- There is a statistically significant effect of electronic bullying on the academic achievement of students, 4- There are no statistically significant differences in the influence of the degree of cyberbullying on academic achievement among male and female secondary school students due to gender. 5- There are no statistically significant differences in the influence of the degree of cyberbullying on academic achievement among male and female secondary school students due to academic grades.
Keywords: cyberbullying; educational attainment; secondary school